Real-World Patterns of Pharmacotherapeutic Management of Asthma Patients With Exacerbations in the Spanish National Health System - Hurtado, Isabel; García-Sempere, Anibal; Peiró, Salvador; Bengoetxea, Asier; Prieto, Jesús Luis; Sanfélix-Gimeno, Gabriel (Frontiers in Pharmacology, 2020)
Background: little is known about the real-world characteristics of asthma patients with exacerbations or their pharmacotherapeutic management. We described the sociodemographic and clinical characteristics, and the patterns of short and long-term management of asthma attacks, in a population-wide cohort of exacerbators in the region of Valencia, Spain. Methods: we selected asthma patients with at least one exacerbation in 2015 and 2016, we classified them according to their patterns of exacerbations in the four years previous to the index exacerbation and their therapeutic step at baseline based on medication received in the previous year. We described the short and long-term pharmacological management of the index exacerbation. Results: 18,714 patients experienced at least one exacerbation. The majority had no previous exacerbation(46.5%), or exacerbated in only one of the years (26.8%). 2.9% had attacks every single year, 25.7% of whom only received rescue medication at baseline. 29.5% of patients without previous exacerbation received maintenance therapy at baseline. Shortly following the index exacerbation, 2,461 patients (13.1%) did not receive any asthma prescription. Among those treated, 70.3% were prescribed a maintenance therapy, 62.4% received a rescue medication and 30.5% received an oral corticoid. Throughout the year following the index exacerbation, most patients remained in their baseline therapeutic step. Conclusions: most patients that exacerbate present very mild to mild forms of the disease or low levels of treatment and mostexacerbations are managed in primary care.. These insights may help to refine strategies for improving asthma control in the population.